2018
DOI: 10.1080/10942912.2018.1503299
|View full text |Cite
|
Sign up to set email alerts
|

Visual detection of apple bruises using AdaBoost algorithm and hyperspectral imaging

Abstract: Hyperspectral imaging technique (400-1000 nm) was used for rapid and nondestructive recognition of bruises of apples. A total of 324 hyperspectral images were collected from 108 Fuji apples and the average spectral reflectance was extracted from the region of interest (ROI) of each image. The classification results of AdaBoost for the data pretreated by various existing methods were compared. Then, the correlation-based feature selection (CFS) algorithm was used to obtain characteristic wavelengths for reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…[68]. The sugar content of apples was reflected via the absorption valley at 820 nm [37]. When an apple bruise develops, the cells in the apple tissue are damaged and the intercellular air spaces decrease, causing differences in water content between bruised and sound regions [69].…”
Section: Image Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[68]. The sugar content of apples was reflected via the absorption valley at 820 nm [37]. When an apple bruise develops, the cells in the apple tissue are damaged and the intercellular air spaces decrease, causing differences in water content between bruised and sound regions [69].…”
Section: Image Processing Methodsmentioning
confidence: 99%
“…This study used a post-processing method that discriminated sound regions from bruised regions, based on the glare from the apple surface, with an accuracy of 98%, see Figure 1.2-5. Bruised regions on 'Golden Delicious' apples were detected by multiple wavebands between 400 and 1000 nm [35], and the Ada-Boost algorithm were developed for detecting bruises on Fuji apples through visible and near infrared wavelengths [37], see Figure 1.2-6. These studies focused on determining only one, or the best, key-wavelength for bruise detection.…”
Section: Evaluation Of Surface Defectsmentioning
confidence: 99%
“…Another challenge in hyperspectral data analysis is data redundancy due to the continuous nature of wavelengths and their similarity. This has been alleviated by the selection of effective wavelengths using algorithms such as the successive projections algorithm (SPA), genetic algorithm (GA), the Monte-Carlo uninformative variable elimination (MC-UVE), and boosted regression tree (BRT) which is also a ML technique [ 81 , 82 , 83 ].…”
Section: Application Of Artificial Intelligence In Phenotyping Technologiesmentioning
confidence: 99%
“…While applying this technology, it is necessary to implement a preprocessing method to reduce the interference signal and highlight the characteristic information of the spectra. Savitzky-Golay (SG) [24], first derivative (FD) [25], multiple scattering correction (MSC) [26], and standard normal variate (SNV) [27] methods have been proven to be effective in spectrum pretreatment. It was shown that these methods could reduce the influence of external factors and improve the detection accuracy to some extent [28].…”
Section: Introductionmentioning
confidence: 99%